Molecular evidence confirms occurrence of Rhipicephalus microplus Clade A in Kenya and sub-Saharan Africa - Esther G. Kanduma; David Emery; Naftaly W. Githaka; Edward K. Nguu; Richard P. Bishop; Jan Šlapeta (Parasites & Vectors, 2020)
Abstract Background The tick vector Rhipicephalus microplus which transmits Babesia spp. and rickettsial pathogens has not been reported in Kenya since 1998. More recently, the pathogenic Babesia bovis has been detected in cattle blood DNA. The status of R. microplus in Kenya remains unknown. This study employed morphological and molecular tools to characterize R. microplus originating from Kenya and assess the genetic relationships between Kenyan and other African R. microplus genotypes. Methods Ticks were collected in south-eastern Kenya (Kwale County) from cattle and characterized to investigate the existence of R. microplus. Genetic and phylogenetic relationships between the Kenyan and other annotated R. microplus reference sequences was investigated by analysis of the cytochrome c oxidase subunit 1 (cox1) gene. To further characterize Kenyan ticks, we generated low coverage whole genome sequences of two R. microplus, one R. decoloratus and R. appendiculatus. A B. bovis specific TaqMan probe qPCR assay was used to detect B. bovis in gDNA from R. microplus ticks. Results Occurrence of R. microplus was confirmed in Kwale County, Kenya. The Kenyan R. microplus cox1 sequences showed very high pairwise identities (> 99%) and clustered very closely with reference African R. microplus sequences. We found a low genetic variation and lack of geographical sub-structuring among the African cox1 sequences of R. microplus. Four complete mitochondrial (mt) genomes for two R. microplus, one R. decoloratus and one R. appendiculatus were assembled from next generation sequence data. The mitochondrial genome sequences of the two Kenyan R. microplus ticks clustered closely with reference genome sequences from Brazil, USA, Cambodia and India forming R. microplus Clade A. No B. bovis was detected in the Kwale R. microplus DNA. Conclusions These findings confirm the presence of R. microplus in Kenya and suggest that R. microplus Clade A is prevalent in cattle in sub-Saharan Africa. These and other recent findings of widespread occurrence of R. microplus in Africa provide a strong justification for urgent surveillance to determine and monitor the spread of R. microplus and vector competence of Boophilus ticks for B. bovis in Africa, with the ultimate goal of strategic control.